2022
DOI: 10.1111/inr.12764
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of Spanish nurses working during the COVID‐19 pandemic: A cross‐sectional study

Abstract: Aim: To explore the impact of the COVID-19 pandemic on the mental health of nurses working in primary, secondary, and tertiary healthcare centers in Navarre (Spain). Background: Healthcare workers, especially nurses, are at high risk for developing mental health problems during the COVID-19 pandemic. Introduction: Spain ranks among the European countries with the highest incidence of and mortality from COVID-19 and has a 31% deficit in the number of nurses compared with the average for the European Union. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 42 publications
1
9
0
1
Order By: Relevance
“…Our study supported previous research and systematic reviews that physical activity is positively associated with reduced occurrence of depression/anxiety disorders and poor physical health outcomes [41][42][43][44]. Individuals who do regular physical activity were found to be less unhappy compared to those who did not exercise during COVID-19 [7,45].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our study supported previous research and systematic reviews that physical activity is positively associated with reduced occurrence of depression/anxiety disorders and poor physical health outcomes [41][42][43][44]. Individuals who do regular physical activity were found to be less unhappy compared to those who did not exercise during COVID-19 [7,45].…”
Section: Discussionsupporting
confidence: 89%
“…Healthcare workers also shared that they are experiencing trouble with sleep (70%), physical exhaustion (68%) and work-related dread (63%) [6]. Likewise, a cross-sectional study using a self-administered online questionnaire involving 800 nurses in Spain found that 68% had some level of depression, anxiety, insomnia, and distress, and of these, 38% had moderate or severe symptoms that highly impacted those who worked in COVID-19 hospital units and in nursing homes [7]. Similarly, an American survey that investigated nurses' perceptions of working during the early stages of the pandemic found that more than 50% of respondents experienced symptoms of depression and anxiety and close to one-third had symptoms of post-traumatic stress disorder [8].…”
Section: Nurses' Mental Health and Coping During The Covid-19 Pandemicmentioning
confidence: 99%
“…4. Tool IV: A structured knowledge quiz about moral and moral matters in healthcare, created by (Martin-Rodriguez et al (2022) and updated by the researcher to evaluate nurses' ethical and moral knowledge. There were 35 multiplechoice questions divided into three sections.…”
Section: Data Collection Toolsmentioning
confidence: 99%
“…The symptoms included a high rate of anxiety, depression, insomnia [32]. Nurses felt as if they were overlooked and lacked support from organizations [33]. Those who worked in hospital COVID-19 units and nursing homes experienced a higher impact on their mental health [34].…”
Section: Introductionmentioning
confidence: 99%